Stability of the B-Glucuronidase Gene in a RO Population of Grape (Vitis ruspestris S.) - Martinelli, L.; Mandolino, G. (South African Journal of Enology and Viticulture, 2017)
A study on the stability of the 6-glucuronidase gene has been conducted in a population of transgenic plants regenerated from somatic embryos of Vitis rupestris S. Molecular tests demonstrated no loss of the inserted gene following either the long-term embryo culture and the plant regeneration events. Dot-Blot analysis proved to be a useful assay for a simultaneous assay of the exogenous gene in the population, and Southern Blot analysis showed the marker gene in the inserted form with a agreeable efficiency (92 % ).